Penyu: Sistem Pendukung Keputusan untuk Penyewaan Ruko yang Strategis Menggunakan Metode Analytical Hierarchy Process(AHP) - Fitra Ramadhan; Maksum Ro’is Adin Saf (Journal of Applied Informatics and Computing, 2020)
In the current economic development in Indonesia, the business in renting shop house is very fast, and to rent a shop house must be in accordance with the target to be achieved, such as a busy location, easily accessible location, or complete shop to maximize service. However, from the aforementioned criteria, the possibility of error in renting a shop house can arise due to lack and limitations in getting shop information. From this problem, a Decision Support System for Strategic Shop House Rentals was built. The method used is the Analytical Hierarchy Process (AHP). Then, three systems were tested, namely black box testing, usability testing and comparison of manual and system calculations. The black box test results obtained with the Equivalence Class Partitioning technique that all input runs, and with the Boundary Value Analysis technique the upper and lower limit values of each input are obtained. Based on the results of the recapitulation of the questionnaire to the user, respondents agreed with satisfaction in using the system with an average of 75.31%.